2013
DOI: 10.1371/journal.pntd.0002365
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary History and Phylogeography of Rabies Viruses Associated with Outbreaks in Trinidad

Abstract: Bat rabies is an emerging disease of public health significance in the Americas. The Caribbean island of Trinidad experiences periodic outbreaks within the livestock population. We performed molecular characterisation of Trinidad rabies virus (RABV) and used a Bayesian phylogeographic approach to investigate the extent to which outbreaks are a result of in situ evolution versus importation of virus from the nearby South American mainland. Trinidadian RABV sequences were confirmed as bat variant and clustered w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 39 publications
2
31
1
Order By: Relevance
“…The vampire bat ( Desmodus rotundus ), which is the main rabies reservoir on the neighboring island of Trinidad and several Latin American countries does not occur on Grenada [18] , [36] . Other bat species are lyssavirus reservoirs worldwide [37] and 13 species of insectivorous and fructivorous bats have been recorded in Grenada [38] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vampire bat ( Desmodus rotundus ), which is the main rabies reservoir on the neighboring island of Trinidad and several Latin American countries does not occur on Grenada [18] , [36] . Other bat species are lyssavirus reservoirs worldwide [37] and 13 species of insectivorous and fructivorous bats have been recorded in Grenada [38] .…”
Section: Discussionmentioning
confidence: 99%
“…These Caribbean variants are quite different from those circulating in mongooses in Asia [13] . In contrast, on the south Caribbean island of Trinidad, rabies circulates in vampire and other bat species, but rabies has not been reported in the Trinidadian mongoose population [18] .…”
Section: Introductionmentioning
confidence: 93%
“…In Trinidad, bat surveillance has traditionally targeted hematophagous bats with Desmodus species comprising the vast majority of tested bats [22,27]. However, the prevalence of RVNA in non-hematophagous bats found in this study suggests an expansion of rabies diagnostic testing to non-hematophagous species may be warranted to obtain a comprehensive picture of rabies host diversity and viral dynamics and ultimately determine the risk of transmission [31].…”
Section: Public Health Implicationsmentioning
confidence: 84%
“…The island is enzootic for bat RABV which has been so far isolated from nine bat species [19,20]. Of these, the hematophagous Desmodus rotundus species is considered the most effective vector on account of its feeding practices [21] and to date, is the only bat directly implicated in transmission of the virus on the island [22]. Some earlier unconfirmed studies have suggested that apparently healthy bats could harbour and transmit RABV for extended periods [23][24][25][26], however to date this has not been conclusively proven by modern diagnostic methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation